Conducted EMI filter design for a switched-mode power supply - Garcia, John David R
Switched-mode power supplies (SMPS) used in industry and sold in the market must be able to satisfy the limits on conducted emissions imposed by law and different international standards. One of the several research areas on conducted EMI is the development of conducted EMI filters. A systematic algorithm for the design of conducted EMI filters for an SMPS has been developed in this study. The algorithm is a systematic iterative process that determines the filter component values of the filter through simulations conducted in MATLAB and actual tests based on the measured power supply noise spectrum. The algorithm addresses the limitations of existing EMI filter design procedures that neglect the effect of the noise source impedance and assumes that the baseline emissions as the noise to be attenuated. The algorithm models the magnitude of the noise source and the noise source impedance and uses these to design the conducted EMI filter. In addition, the algorithm does not require information on the topology and control of the SMPS. The algorithm was used to design a conducted EMI filter for the power supply SYNERGY (Input ratings: 110V, 1.3kW) and comply with the CISPR22 Class B standard. It was shown that the EMI filter recommended by the algorithm was able to satisfy the standard.